2001
DOI: 10.1074/jbc.m107134200
|View full text |Cite
|
Sign up to set email alerts
|

B-lymphocytes from Malignant Hyperthermia-susceptible Patients Have an Increased Sensitivity to Skeletal Muscle Ryanodine Receptor Activators

Abstract: Malignant hyperthemia (MH) is a pharmacogenetic disease triggered by volatile anesthetics and succinylcholine in genetically predisposed individuals. The underlying feature of MH is a hypersensitivity of the calcium release machinery of the sarcoplasmic reticulum, and in many cases this is a result of point mutations in the skeletal muscle ryanodine receptor calcium release channel (RYR1). RYR1 is mainly expressed in skeletal muscle, but a recent report demonstrated the existence of this isoform in human B-lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(65 citation statements)
references
References 44 publications
4
60
1
Order By: Relevance
“…Recently it was shown that RyR1s are also expressed in other cell types, including neurons, smooth muscle cells and immune cells, specifically in Blymphocytes and dendritic cells (DC) (Sei et al, 1999;Girard et al, 2001;Bracci et al, 2007;Uemura et al, 2007;O'Connell et al, 2002). DCs are the most potent antigen presenting cells connecting innate and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently it was shown that RyR1s are also expressed in other cell types, including neurons, smooth muscle cells and immune cells, specifically in Blymphocytes and dendritic cells (DC) (Sei et al, 1999;Girard et al, 2001;Bracci et al, 2007;Uemura et al, 2007;O'Connell et al, 2002). DCs are the most potent antigen presenting cells connecting innate and adaptive immunity.…”
Section: Introductionmentioning
confidence: 99%
“…They are located in peripheral tissues where they continuously sample the environment for the presence of foreign antigens; when these are encountered DCs process them and then migrate to secondary lymphoid organs where they present the processed antigens in conjunction with major histocompatibility complex II (MHCII) molecules to T-lymphocytes and initiate a specific immune response (Banchereau et al, 2000). Studies on the role of RyR1 in immune cells in vitro has established that in B-lymphocytes its activation is coupled to cytokine release (Girard et al, 2001) whereas in DCs it leads to enhanced maturation, release of proinflammatory cytokines and enhanced ability to prime T-cells (Bracci et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To examine the function of RYR1 channel variants in EBV-immortalized lymphoblastoid cells, we recorded extracellular acidification, as a measure of the energy metabolism of activated cells, with a sensitive pHmetric biosensor. RYR1 is expressed in human B lymphocytes where it functions as a CaP [Sei et al, 1999], and CaP 2+ P homeostasis is altered in B cells of MHS individuals [Sei et al, 2002;Girard et al, 2001]. We demonstrate that the increase in the acidification rate of immortalized lymphoblastoid cells in response to 4-CmC is mainly due to the activation of the RYR1 calcium channel; therefore this assay can be used to analyze the activity of RYR1 in this cellular system.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have also demonstrated that human B-lymphocytes express RYR1 [Sei et al, 1999] and could be used as a model to test the effect of sequence variants on RYR1 function [Sei et al, 2002[Sei et al, , 1999Girard et al, 2001]. We therefore applied the proton release assay in EBV-immortalized lymphoblastoid cells from patients carrying RYR1 variants.…”
Section: Proton Release Measurements In Ebv-immortalized Normal Lymphmentioning
confidence: 99%
See 1 more Smart Citation